Factors of Incidence of Hypertension in Southwest Sumba - Kaka, Apliana Lupu; Salmun, Johny A.R; Budi, Agus Setyo (Faculty of Public Health, Nusa Cendana University, 2020)
Hypertension in conditions when blood pressure is at a value of 130/80 mmHg or more with the number of cases experiencing an increase from 2016-2018, Tana Mete Village, Kodi Balaghar District. in 2016 there were 880 (8.8%), cases in 2017 were 2,580 (25.8%) cases and in 2018 there were 3. 410 (34.1%) cases. Hypertension in influenced by factors of age, smoking habits, stress, and alcohol consumption. This study aims to analyze the relationship between age, smoking habits, stress, and alcohol comsuption. This research is an analytic observational research with a case control research design. The number of cases in Tana Mete Village, Kodi Balaghar District, Southwest Sumba Regency was 220 (22%) and the sample was 80 respondents and divided into two groups, namely the case and control group, the case group was 40 respondents and the control group was 40 respondents. These variables have been analyzed univariately and bivariately, the results of this study incidate that there are three risk factor variables for the incidence of hypertentsion. Namely age with a value p= 0.003, OR=4.059 (95% CI: 1.568-10.510), smoking habits with a value p=0.001, OR: 6.378 (95%CI:2.280-17.842), stress with a value of p=0.014, OR: 3.095 (95%CI: 3.095-7.706) while the variable alcohol comsumption has no relationship with the value of p=0.133. To prevent the occurrence of hypertension, the activities undertaken include avoiding smoking, stress and taking time for recreation.